BREAK EVENT POINT (BEP) USAHA AYAM KAMPUNG SECARA EKSTENSIF DAN SEMI INTENSIF - Sapta, Endang (AgriSains, 2014)
This study was aimed to obtain information and at the same time comparing the value of Break Event Point (BEP) of farm chicken of the two systems maintenance carried out by the people of Tulungagung, i.e: extensive and semi-intensive systems.The analysis based on two value of BEP: 1). BEP revenue  and 2).BEP of egg production per month.A survey method was applied inthis research. The location determined by purposive based on the level of the chicken ownership. Research units were chicken farmers, while research objects werechicken farm. Sampling techniques forfarm chicken was bussiness  respondents  with extensive system was based on quota sampling technique,while for semi-intensive system based on the total sampling technique. The number of respondents of an extensive business system as much as 167 respondents, while the semi-intensive business only 2 people.The average number of chickens from extensive business as much as 9 chickens (7 females and 2 males), while for semi-intensive businesses as much as 428 chickens (400 females and 28 males).The results showed that the value of BEP revenue of  extensive business  was Rp 2.503.3, while for semi-intensive business  was Rp 1.737.818.  The BEP value of egg production  for extensive business system was 2 eggs, while for semi-intensive businesses system was 1.069 eggs.Based on theBEP analysis, both bussiness systemswere beneficial, guarantee and feasible to be developed. Keywords : Chicken, extensive and semi-intensive system, break event point.